CONHECIMENTO ESPECÍFICO DE BIOLOGIA E A TEMÁTICA CORPO HUMANO: DESAFIOS DOCENTES ANTE À DEFICIÊNCIA VISUAL - Canto, Maria Guadalupe Couto do (2023)
The present study is inserted in the line of research Teacher training in Science and Mathematics of the Graduate Program in Science and Mathematics Teaching (PPGECIMAT), of the Franciscan University (UFN). Society has come to recognize and include individuals who were previously practically segregated from the educational process, requiring improvement of teachers and techniques to the needs of this public, in order to include it in education for all. Problematizing about the quality of the specific knowledge of Biology among undergraduate students of the area, and their perspectives of approach with the students, this study outlined the objective of investigating the specific knowledge of the content, more specifically of the theme Human Body, of the undergraduate students in Biological Sciences, considering their inclusive approach. To this end, it fulfilled the specific objectives that include describing the elements of the theory aimed at teaching, in the view of Lee Shulman; present formal, theoretical and pedagogical aspects of the teaching of the Human Body theme in the classroom; to describe the epistemological findings related to the teaching of people with disabilities, especially those with visual impairment; and to ascertain, together with undergraduate students in Biological Sciences, the specific knowledge of the content, having the theme Human Body as a guiding thread, to be mediated with students in the inclusive perspective. Making use of discursive textual analysis, and implicative statistical analysis, with the use of dynamics together, and data collected in dynamics records and questionnaires, submitted via the Googles Forms platform, the investigation also made use of a collaborative technique, developed throughout a training course with undergraduate students of Biological Sciences. The findings, which include the importance of promoting inclusion, allowed us to infer that training, when not adequate, can impact compliance with the inclusive principle, since it presupposes losses or deficiencies in the educational process; undergraduates believe that even if the common class receives adaptations for the different demands of special educational needs, there is no way to make adjustments to the needs of all students, limiting the possibilities of inclusive education, but they believe that disability does not constitute impediments to learning. In addition, it is observed that the traditional training model for teaching Science and Biology may be deficient, needing to be adapted for an effective mediation of knowledge among people with disabilities.